دور القيادة الإدارية في تطوير الثقافة التنظيمية للمؤسسة: حالة مؤسسة سونلغاز فرع معسكر - علي شريف, حورية; بلحمو, خديجة (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة لتبيان دور القيادة الإدارية في تطوير الثقافة التنظيمية للمؤسسة، من خلال أبعاد الاتصال، التحفيز، المشاركة في اتخاذ القرار، فعالية فرق العمل، الإبداع والابتكار. لقد استخدمنا المنهج الوصفي التحليلي لذلك مستعينين بمجموعة من المراجع، ومستخدمين الاستبيان على مؤسسة سونلغاز فرع معسكر، فكانت النتائج التالية: أن هناك ارتباطا بين أبعاد القيادة الادارية والثقافة التنظيمية، وكان التأثير لبعد العمل بروح الفريق يدل على اهتمام المؤسسة به أكثر نظرا لطبيعة نشاطها. Abstract: The study aims to show the role of administrative leadership in the developing of the organizational culture of the company through the dimensions of communication, motivation, participation in decision-making, efficiency of work teams, creativity and innovation. We have used the descriptive analytical method, using a group of references, and using the questionnaire on the Sonelgaz Company of Mascara. The results were as follows: there is a correlation between the dimensions of administrative leadership and the organizational culture, and the effect of the dimension of teamwork indicates its interest in the company due to the nature of its activities.
The role of administrative leadership in the development of organizational culture of the company: case of the Sonelgaz Company of Mascara
Keywords: قيادة ادارية ; ثقافة تنظيمية ; مؤسسة سونلغاز فرع معسكر; administrative leadership ; organizational culture ; sonelgaz company of mascara